1983
DOI: 10.1515/znb-1983-1104
|View full text |Cite
|
Sign up to set email alerts
|

Metallkomplexe mit Tetrapyrrol-Liganden, XXXI [1]. Neutrale und anionoide Bisporphinate des Gers und Praseodyms / Metal Complexes with Tetrapyrrole Ligands, XXXI [1]. Neutral and Anionoid Bisporphinates of Cerium and Praeseodymium

Abstract: Abstract The preparation of the lanthanoid bisporphinates, bis[meso-tetra(p-tolyl)porphinato]-cerium(IV) [Ce(TTP)2**] and bis[meso-tetra(p-tolyl)porphinato]hydrogenpraseodymium-(III) [PrH(TTP)2] from Ce(acac)3 and Pr(acac)3 in boiling 1,2,4-trichlorobenzene is described. Ce(TTP)2 is a diamagnetic and rather inert CeIV derivative, PrH(TTP)2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 6 publications
(8 reference statements)
1
25
0
Order By: Relevance
“…The comparison of the electronic spectrum of LuPcNc with those of LuPc 2 and LuNc 2 (Nc 2À = naphthalocyaninato) suggested an assymetry of the electron density over this unsymmetrical bismacrocyclic complex [5,6]. Similar sandwich complexes are known for porphyrins [7,8] and a lot of effort has been put into the synthesis and studies of heteroleptic complexes associating two different porphyrins [9,10], or two dissimilar phthalocyanines, or a phthalocyanine and a naphthalocyanine [11,12]. From near-infrared and Raman spectroscopies, it has been concluded that the oxidized macrocycle of a heteroleptic double-decker complex, coupling a phthalocyanine and a porphyrin, is the phthalocyanine (Pc ÅÀ ) and that the molecular orbital levels retain their P or Pc nature [11,[13][14][15].…”
mentioning
confidence: 54%
“…The comparison of the electronic spectrum of LuPcNc with those of LuPc 2 and LuNc 2 (Nc 2À = naphthalocyaninato) suggested an assymetry of the electron density over this unsymmetrical bismacrocyclic complex [5,6]. Similar sandwich complexes are known for porphyrins [7,8] and a lot of effort has been put into the synthesis and studies of heteroleptic complexes associating two different porphyrins [9,10], or two dissimilar phthalocyanines, or a phthalocyanine and a naphthalocyanine [11,12]. From near-infrared and Raman spectroscopies, it has been concluded that the oxidized macrocycle of a heteroleptic double-decker complex, coupling a phthalocyanine and a porphyrin, is the phthalocyanine (Pc ÅÀ ) and that the molecular orbital levels retain their P or Pc nature [11,[13][14][15].…”
mentioning
confidence: 54%
“…[93] The reaction between H 2 TPP and UO 2 (OAc) 2 in molar ratio 1:10 in a refluxing benzonitrile medium during 19 hours yields two complexes U(TPP) 2 The NMR spectrum of the double-decker complex agrees with the literature data for Th IV (TPP) 2 [88] and Ce IV (TTP) 2 (TTP -tetratolylporphyrin dianion). [94] The NMR spectrum of the triple-decker complex shows ten peaks what is in accord with ten kinds of protons: two -C 4 H 2 N (one inner and two outer macrocycles), two -p-C 6 H 5, threeo-C 6 H 5, and three -m-C 6 H 5 .…”
Section: T N Lomova Et Almentioning
confidence: 94%
“…1). The first examples of homoleptic bis(porphyrinato) and heteroleptic porphyrinato and phthalocyanato complexes appeared in the 1980s [18,19]. The tetrapyrrole-based sandwich-type complexes have great potential in the preparation of different devices such as an enzyme-free electrochemical sensor for dopamine detection based on the (phthalocyaninato) (porphyrinato) europium III double-decker complex [20] and spintronic devices [21].…”
Section: Sandwich-type Complexesmentioning
confidence: 99%